Hakikat Kepemimpinan Transformasional - Qoyyimun Nafal; Binti Maunah; Achmad Patoni (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to explore and understand the nature of transformational leadership. Transformational leadership focuses on efforts to inspire, motivate, and develop team members to achieve positive change in the organization. This type of leadership involves leaders who are able to direct a clear vision, create an environment that supports innovation, and pay attention to the needs of individuals to reach their maximum potential. The main characteristics of transformational leadership include four main components: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This research uses a descriptive and analytical approach through a comprehensive literature review to collect, select and analyze relevant literature. It is hoped that the research results will provide in-depth insight into leadership theory and offer guidance for practitioners in increasing leadership effectiveness in their organizations.